Experimental Study of Hydroformed Al6061T4 Elliptical Tube Samples under Different Internal Pressures - Md. Meraz; Santosh Kumar; Ravi Prakash Singh (EMITTER International Journal of Engineering Technology, 2022)
In order to achieve crack free elliptical shape under controlled conditions, an experimental set-up was designed and fabricated. This setup consists of three hydraulic cylinders, an intensifier, a hydraulic power pack, storage tanks, forming die, and all parts are controlled by a Programmable Logic Controller (PLC) system. The elliptical samples can be achieved through proper control of internal pressure and axial force with proper sealing. Experimental work has been carried out with different magnitudes of internal pressure and constrained conditions of axial force. Initially die of elliptical shape has been designed and modeled in Abaqus to successfully achieve the particular shape of the Al6061T4 tube under different internal pressure. The fabricated tube hydroforming machine set-up is highly effective for forming 0.5 mm-2 mm thick Al6061T4 alloy tube samples. The Experimental test has been carried out at 12.7 mm outer diameter, 175 mm length and 0.5 mm thick Al6061T4 samples. Bulge height parameters measured at different points of regular distance gap on the axial direction of the tube length and corner radius found at different pressures range of the samples are plotted under different internal pressures. Samples having an 18.7 mm major elliptical bulge were achieved during the experiment. The experimental data was validated by simulation results.